2019
DOI: 10.3354/meps13067
|View full text |Cite
|
Sign up to set email alerts
|

Integrating remote sensing and diver observations to predict the distribution of invasive lionfish on Bahamian coral reefs

Abstract: Pacific lionfish (Pterois sp.) in a reef crevice in Eleuthera, The Bahamas, which is part of the invaded Caribbean range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…In contrast to other invasive species, where shelter use of the invasive is unchanged in the presence of native species [42,111], we found that lionfish reduced their shelter use in the presence of lobsters or Diadema. Our findings lend support to anecdotal evidence that reefs with high urchin densities support few lionfish [57], potentially because urchins occupy all available shelters. In our lionfish-lobster together trials we found an effect of prior residency, where lionfish were less likely to dominate a shelter if a lobster occupied the shelter first.…”
Section: Impacts Of Lobsters and Diadema On Lionfishsupporting
confidence: 83%
See 3 more Smart Citations
“…In contrast to other invasive species, where shelter use of the invasive is unchanged in the presence of native species [42,111], we found that lionfish reduced their shelter use in the presence of lobsters or Diadema. Our findings lend support to anecdotal evidence that reefs with high urchin densities support few lionfish [57], potentially because urchins occupy all available shelters. In our lionfish-lobster together trials we found an effect of prior residency, where lionfish were less likely to dominate a shelter if a lobster occupied the shelter first.…”
Section: Impacts Of Lobsters and Diadema On Lionfishsupporting
confidence: 83%
“…This could lead to lionfish displacing lobsters and Diadema from shelters, thus exposing them to greater predation risk. Similar shelter preferences between lionfish, spiny lobsters and Diadema have been suggested [ 57 ], and shelter use interactions between lionfish and lobsters are believed to occur. Lionfish are highly abundant by-catch species in lobster traps [ 58 ] and the presence of lionfish is associated with lower lobster abundance in both traps [ 59 ] and condos (non-enclosed shelter traps; [ 60 , 61 ]).…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The presence of lionfish may also deter native species, as suggested by higher lionfish and lower native species recruitment in shorter soak times and the opposite with longer soak times. Higher lionfish recruitment and catch from single trap deployments disproved our hypothesis that paired deployments could synergistically recruit more lionfish, given lionfish are often found in groups [55] and aggregating behavior is driven by broad-scale habitat complexity [56,57]. Counterintuitively, our results indicated that lionfish density on the adjacent artificial reef was not a significant predictor of lionfish recruitment nor catch.…”
Section: Discussionmentioning
confidence: 47%